Aligning restoration science and the law to sustain ecological infrastructure for the future. Issue 9 (1st November 2015) - Palmer, Margaret A; Ruhl, JB
Abstract : Ecological restoration as grounded in modern science is based on a systems perspective – it seeks to recover ecological systems characteristic of past or least‐disturbed contemporary landscapes. This requires recovery of organisms along with the ecosystem features and dynamic processes that support them. Since self‐sustainability is the goal, it also requires a landscape and environmental context that supports recovery of the system. As restoration becomes more widely practiced, so too are many specialized forms of environmental intervention, such as those associated with reducing the impacts of development, promoting recovery of endangered species, and achieving compensatory mitigation. These may be valuable and may also be informed by ecological science but they differ substantially from ecological restoration because they are not necessarily focused on recovery of a self‐sustaining living system characteristic of past or least‐disturbed landscapes. The US legal system has failed to make this distinction. Federal statutes do not explicitly define restoration and in fact do little to constrain or even guide this process; if this is not rectified, net ecological losses will continue to occur. Scientists and policy makers can add precision to the use and practice of ecological restoration and other, more specialized forms of restoration, to ensure a future that can support ecosystems and the people that depend on them.